“AN EMPERICAL INVESTIGATION OF EMPLOYEE EMPOWERMENT AS A DETERMINENT OF ORGANIZATIONAL COMMITTMENT WITH SPECIAL REFERENCE TO EMPLOYEES OF BHILAI STEEL PLANT” (International Journal of Food and Nutritional Sciences, 2022)
The research paper focus is on exploring the relationship between employee empowerment and organizational commitment among Bhilai Steel Plant's employees. Skilled and empowered employees are becoming increasingly critical to the success of an organization. When an employee is empowered, they feel comfortable sharing their ideas, which can lead to improved job performance.In knowledge-based companies, successful teams possess a crucial attribute, which is a considerable amount of decision-making power or empowerment. Empowered workers are an asset to any organization because they are self-motivated and driven to perform their duties well. The aim of this research is to determine the effects of employee empowerment.